Analisis Standar Penilaian Pendidikan di Indonesia - Noven Kusainun (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
One important factor in the education system is assessment. Educational assessment must have clear and operational standards. Education assessment standards in Indonesia are regulated in Permendikbud Number 23 of 2016 consisting of 8 chapters and 15 articles. The purpose of this study is to analyze the criteria in the educational assessment standards in Indonesia. This research uses a literature study method with technical analysis in the form of content analysis. The results showed that the standard of education assessment in Indonesia has included clear criteria in the assessment. Assessment criteria include the scope, objectives, benefits, principles, mechanisms, procedures, and instruments of assessment of student learning outcomes. These criteria serve as guidelines in assessments conducted by educators, education units, and the government.